Destabilized Passivation Layer on Magnesium-Based Intermetallics as Potential Anode Active Materials for Magnesium Ion Batteries - Matsui, Masaki; Kuwata, Hiroko; Mori, Daisuke; Imanishi, Nobuyuki; Mizuhata, Minoru (Frontiers in Chemistry, 2019)
Passivation of magnesium metal anode is one of the critical challenges for the development of magnesium batteries. Here we investigated the passivation process of an intermetallic anode: Mg3Bi2 synthesized by solid-state and thin film process. The Mg3Bi2 composite electrode shows excellent reversibility in magnesium bis(trifluoromethansulfonylamide) dissolved in acetonitrile, while Mg3Sb2, which has same crystal structure and similar chemical properties, is electrochemically inactive. We also fabricated the Mg3Bi2 thin film electrodes, which show reversibility with low overpotential not only in the acetonitrile solution but also glyme-based solutions. Surface layer corresponding to the decomposed TFSA anion is slightly suppressed in the case of the Mg3Bi2 thin film electrode, compared with Mg metal. Comparative study of hydrolysis process of the Mg3Bi2 and the Mg3Sb2 suggests that the both intermetallic anodes are not completely passivated. The bond valence sum mapping of the Mg3Bi2 indicates that the fast Mg2+ diffusion pathway between 2d tetrahedral sites is formed. The electrochemical properties of the Mg3Bi2 anode is mainly due to the less passivation surface with the fast Mg2+ diffusion pathways.